Identity and social reproduction in the translocal networks of migrants of two Andean towns - Malengreau, Jacques (2008)
This article contrasts strategies adopted by migrants from two Andeancommunities located in different regions in Peru, in their useof social, cultural, and material networks, taking into consideration the place they settle in and where they come from, their translocal experience. These strategies are embedded in a parallel form; on the one hand there is an extension of the domestic bonds from the original village in the place they finally settle down in, mostly givenby a transgenerational continuation, based on collateral descendance (uncle/aunt – nephew/niece), which weakens the original supradomestic collective identities; and, on the other hand, the newly interethnic neighborhood bonds which transform the social solidarity model in the place they settle down in. These strategies that combine hierarchy, clientelism, reciprocity and redistribution, also imply a new interpretation of norms regulated by the «liberal», productive, competitive and consumer model, conditioned by a foreign world which is manifested in a transnational and transregional form.Hence, these strategies can be seen as a development of common traits, particularities related not only to social-historic and cultural heritage, but also to a type of destination chosen by these migrants, for example metropolitan Lima, the urban and regional centers and the Oriental tropical valleys.